Improving the performance of a commercial absorption cooling system by using ejector: A theoretical study - Hamza K. Mukhtar; Saud Ghani (Case Studies in Thermal Engineering, 2023)
Absorption cooling systems (ACS) have lower coefficients of performance (COP) compared to direct expansion (DX) cooling systems. Nevertheless, ACS offers a green alternative to typical DX systems. In this study, a numerical model was developed for the commercial low-capacity Robur® absorption cooling system (RACS). The model was developed based on mass, concentration, and energy balance equations, in addition to heat transfer equations. The model results were validated against experimental data available in the literature for the same cooling unit yielding a good agreement. Hence, to improve the COP of the RACS, a vapor ejector was introduced between the generator and the condenser. An improvement of 70.6% in the COP was obtained at the design condition. A parametric analysis was implemented to study the significance of the key parameters in the RACS performance. It was found that the increase in the ambient temperature not only increased the activation temperature, but it also decreased the COP and increased the circulation ratio (CR). Consequently, in hot environments, lowering the evaporator temperature is recommended to avoid the need for higher CR. Optimizing the nozzle throat and the mixing tube diameter improves the ejector performance, and hence the RACS performance, as long as the ejector operates under critical conditions. Finally, the absorber coil was found to have the most significance on the RACS performance in comparison with the rectifier coil and the refrigerant heat exchanger.